PENGENALAN E-LEARNING PEMBELAJARAN GURU-GURU MADRASAH IFTIDAIYAH SWASTA BONTOA - Andriani Yasin, Nurfatwa; -, Masmarulan; -, Muliati; -, Rahmat; -, Bahriansyah (Unit Publikasi dan Jurnal Sekolah Tinggi Ilmu Ekonomi Tri Dharma Nusantara Makassar, 2022)
As an effort to prevent the Covid-19 pandemic, the government and its staff issued a policy for schools to carry out learning at home. As of March 16, 2020, the school has implemented the online student learning method. The online learning system (on the network) is a learning system without face to face directly between teachers and students but is carried out online using the internet network. Teachers must ensure that teaching and learning activities continue, even though students are at home. The solution is that teachers are required to be able to design learning media as innovations by utilizing online media (online). Due to the diversity of teacher competency levels in carrying out online learning, it is necessary to socialize the introduction of the learning system. Therefore, in this community service, lecturers who carry out community service try to introduce e-learning learning media by providing examples of how to use it, for example using Google Classroom, and making learning videos uploaded on YouTube. In addition to teachers, lecturers also provide direction, views and motivation to parents because students' parents are considered to have an important role and cooperation in educating children during online learning at home. The result of this community service is that teac hers already know, understand and can manage online classes well e-learning